The Effectiveness of the Polarized Low-Level Laser in the Treatment of Patients With Myofascial Trigger Points in the Trapezius Muscles - Shahimoridi, Dadollah; Shafiei, Seyed ali; Yousefian, Bahram (Journal of Lasers in Medical Sciences, 2020)
Introduction: This study assessed the effect of polarized low-level laser therapy (PLLLT) in the treatment of myofascial trigger points (MTrPs) in the trapezius muscles. Its effectiveness in pain reduction was compared to low-level laser therapy (LLLT). Methods: 64 patients with MTrPs were randomly divided into two groups, namely, PLLLT and LLLT. Each patient received treatment for a period of 2 weeks, 5 sessions a week. The intensity of laser irradiation to the skin surface was 6 J/cm2. The system exit power was 160 mw at 755 nm wavelength. The Visual Analog Scale (VAS) for the 1st, 5th and 10th sessions was analyzed through two-way repeated measures ANOVA. Results: Increasing the number of treatment sessions was effective in reducing pain intensity (P> 0.05). The effect of LLLT in pain reduction was significantly greater than that of PLLLT (P>0.05). Referred pain (RP), limitation of neck movement (LNM), presence of muscular taut band (PMTB) and sensitivity of muscular taut band (SMTB) were reduced significantly by the end of the 10th session, compared with participants’ condition at the beginning of the 1st session in both groups. Conclusion: PLLLT and LLLT can effectively treat MTrPs of the trapezius muscles, especially to reduce RP, LNM, PMTB and SMTB. However, the effect in the LLLT group was significantly greater than in the PLLLT group. In accordance with the observed results, LLLT is recommended as an effective method for treating MTrPs.